Identification case of evidence in timber tracing of Pinus radiate, using high-resolution melting (HRM) analysis. (March 2016) - Solano, Jaime; Anabalón, Leonardo; Encina, Francisco
Abstract: Fast, accurate detection of plant species and their hybrids using molecular tools will facilitate assessment and monitoring of timber tracing evidence. In this study the origin of unknown pine samples is determined for a case of timber theft in the region of Araucania southern Chile. We evaluate the utility of the trnL marker region for species identification applied to pine wood based on High Resolution Melting. This efficient tracing methods can be incorporated into forestry applications such as certification of origin. The object of this work was genotype identification using high-resolution melting (HRM) and trnL approaches for Pinus radiata (Don) in timber tracing evidence. Our results indicate that trnL is a very sensitive marker for delimiting species and HRM analysis was used successfully for genotyping Pinus samples for timber tracing purposes. Genotyping samples by HRM analysis with the trnL1 approach allowed us to differentiate two wood samples from the Pinaceae family: Pinus radiata (Don) and Pseudotsuga menziesii (Mirb.) Franco. The same approach with Pinus trnL wood was not able to discriminate between samples of Pinus radiata, indicating that the samples were genetically indistinguishable, possibly because they have the same genotype at this locus. Timber tracing with HRM analysis is expected to contribute to future forest certification schemes, control of illegal trading, and molecular traceability of Pinus spp.